Pengembangan Kurikulum Pendidikan Agama Islam (PAI) Berbasis Riset Moderasi Beragama Dalam Konteks Pluralitas Masyarakat Kota Balikpapan - Kusnan Dr; Khoirul Anam Siddeh (At-Tarbiyah Jurnal Pendidikan,Kebudayaan dan Keislaman, 2025)
Balikpapan City, East Kalimantan Province, serves as a significant locus of study. In addition to being known as an industrial city with a high degree of ethnic and religious diversity, Balikpapan now holds a strategic status as the main gateway to the Nusantara Capital City (IKN). The dynamic social environment and projected increase in population migration to this area have the potential to intensify cultural friction and differences in religious interpretation. Therefore, the need for an Islamic Religious Education (PAI) curriculum that explicitly fosters attitudes of religious moderation and appreciation of local diversity has become increasingly urgent. This research employs a Research and Development (R&D) approach with the primary focus on producing a research-based PAI curriculum model that internalizes the values of religious moderation, specifically tailored to the context of Balikpapan City. The development of a research-based Islamic Religious Education curriculum emphasizing religious moderation is highly relevant and urgent for the heterogeneous society of Balikpapan. The curriculum model developed through the R&D approach successfully integrates the values of religious moderation contextually into the four main PAI subjects, emphasizing research-based learning methodologies. This model has been evaluated as valid and practical for implementation, and it has the potential to shape students as agents of change who uphold national commitment, reject violence, promote tolerance, and accept local traditions within the framework of wasathiyah (moderate) Islamic teachings.